'Fantôme de devoir': The Princesse de Clèves's Haunting Duty. Issue 1 (2nd January 2020) - Fancy, Benjamin
Abstract : This article explores the ways in which the characters of Marie-Madeleine de Lafayette's La Princesse de Clèves manipulate the conventions surrounding death in seventeenth-century France. It argues that Mme de Chartres prevents her daughter from participating in the traditional ceremonies surrounding death that were intended to comfort the living as much as the dying. In so doing, Mme de Chartres creates a sort of psychic ghost. One such manifestation of this ghost is the term 'devoir, ' one that Mme de Chartres herself used in life. M. de Clèves's later death functions as a rewriting of Mme de Chartres's; it provides an opportunity for the princess to assert herself as an active participant in her husband's deathbed scene, a role which her mother had not previously allowed her to assume. This motivates the princess to retreat to a convent, where no one, not even the narrator, bears witness to her passing.